INFLUENCE OF LENGTH OF SERVICE ON WORKERS' ATITUDE TOWARDS OCCUPADONAL HAZARDS - UGWU, DOROTHY IFEYlNWA, UGWU, DOROTHY IFEYlNWA (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2015)
The study examined the attitude of workers towards occupational hazards and the attitude of long and short serving workers towards occupational hazards in Anambra Motor Manufacturing Company (ANAMCO), Enugu, Nigeria. One null hypothesis was tested at 0.05 level of significant. The population for the study consisted of 521 workers of ANAMCO. The instrument used for the study was Attitude of Workers Regarding Occupational Hazards Questionnaire (AWROHQ). This was designed by the researcher. Stratified sampling and simple random sampling techniques were used to draw sample for the study. Mean, standard deviation and student t-test were used for data analysis. Results revealed that wrote. in ANAMCO Company had favorable attitude towards their workplace hazards; long serving workers showed more favorable attitude than the short serving workers. However, the result revealed no significant difference in the attitudinize of the long and short serving workers towards their hazardous work environment. In view of this, it was recommended, among others, that management should show strong and true commitment to occupational health and safety so that all workers, irrespective of length of service, will improve their attitude regarding safety in their work environment.